Perbandingan Hasil Metode Evaluasi Usability Antara Heuristic Evaluation dengan Think Aloud pada Kasus Web FILKOM APPS untuk Mahasiswa - Mochammad Imam Sya' Roni; Agi Putra Kharisma; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Web FILKOM APPS for students is a medium of information that helps FILKOM students to meet the needs of study, especially for students who do thesis. So far the web has not been evaluated, therefore it is necessary to evaluate the usability of web FILKOM APPS for students, to find out the problems faced by the web, The purpose of this research is to know comparison of evaluation result between heuristic evaluation and think aloud method, Which is expected from the results of this study can provide information to web developers, To improve usability and functionality of existing features. Heuristic evaluation is an evaluation method done by HCI alhi to show usability problem, Whereas the think aloud method is a method of usability evaluation performed by users to be consulted, and expressing their feelings and thoughts when interacting with the interface product. From the evaluation results, for heuristic evaluation methods HCI experts found usability problems related to common interface and some menus that still can not function properly, as well as inconsistent languages. As for the method think aloud users find usability problems such as constraints faced when performing an action / task and problems related to the interface display, the menus are not working properly, and language is not consistent.